Social capital and the health of left-behind older adults in rural China: a cross-sectional study - Yu Chen; Yan Ke; Junfeng Jiang (BMJ Open)
Objective To examine the association between social capital and the health of male and female left-behind older adults in rural China.Study design This cross-sectional study among the left-behind older adults aged 60 and older and with all their children working outside of Hubei, Shaanxi and Guangdong provinces in China was conducted in 2017–2018. A total of 1106 questionnaires were collected (participation rate=100.0%), and questionnaires from 1016 participants were used (effective rate=91.9%).Methods An ordinary least squares model was used to evaluate the association between social capital and health. Social capital included family trust, friend/neighbour trust, stranger trust, social participation, and network size and density. Health outcomes included basic and instrumental activities of daily living (BADL and IADL) and depression.Results Elevated family trust, friend/neighbour trust, stranger trust, high-level participation and middle-level network density were associated with reduced depression (b=−3.23, p<0.001; b=−0.41, p<0.001; b=−0.76, p<0.01; b=−1.04, p<0.05; b=−0.74, p<0.05, respectively). High-level participation and network density were also associated with elevated BADL (b=0.16, p<0.05; b=0.24, p<0.05, respectively). Elevated family trust (b=−2.86, p<0.05 in men; b=−3.86, p<0.001 in women), stranger trust (b=−0.68, p<0.05 in men; b=−0.80, p<0.05 in women) and high-level participation (b=−0.92, p<0.05 in men; b=−1.22, p<0.01 in women) were associated with reduced depression in both sexes. By contrast, elevated friend/neighbour trust was associated with reduced depression (b=−0.56, p<0.001) in women, high-level participation was associated with elevated BADL (b=0.19, p<0.05) and IADL (b=0.43, p<0.05) in men, and high-level network density was associated with elevated BADL (b=0.44, p<0.05) and IADL (b=0.57, p<0.05) and reduced depression (b=−1.05, p<0.05) in women.Conclusions Social capital is closely related to left-behind older adults’ health in rural China. More attention should be paid to increasing the stock of social capital in this special population, with a particular focus on the sex disparity.